2017
DOI: 10.1001/jamadermatol.2016.4361
|View full text |Cite
|
Sign up to set email alerts
|

Teledermatology for the Diagnosis and Management of Skin Cancer

Abstract: IMPORTANCE As technology becomes more commonplace in dermatological practice, it is essential to continuously review the accuracy of teledermatology devices and services compared with in-person care. The last systematic review was conducted over 5 years ago. OBJECTIVE To synthesize and assess the quality of the evidence to address 3 research questions: (1) How accurate is teledermatology for skin cancer diagnosis compared with usual care (face-to-face [FTF] diagnosis)? (2) Does teledermatology save clinician a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
168
0
11

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 203 publications
(188 citation statements)
references
References 40 publications
9
168
0
11
Order By: Relevance
“…However, quality assurance for teledermatology is vital to deliver adequate healthcare. This requires to test teledermatological applications for feasibility, quality, safety and accuracy …”
Section: Introductionmentioning
confidence: 99%
“…However, quality assurance for teledermatology is vital to deliver adequate healthcare. This requires to test teledermatological applications for feasibility, quality, safety and accuracy …”
Section: Introductionmentioning
confidence: 99%
“…To try to alleviate this, clinical or dermoscopic images can be added to referrals to improve their usefulness. These methods, teledermatology (TD) and teledermoscopy (TDS), can ensure that patients with malignant lesions are cared for without unnecessary delay, while decreasing the need for patients with benign lesions to see a dermatologist face‐to‐face (FTF) …”
Section: Introductionmentioning
confidence: 99%
“…A previous review reported people would be willing to pay out of pocket expenses for access to teledermatology services [30]. Spinks et al [31] conducted a discrete choice experiment to investigate consumer preferences for melanoma screening options using different health services compared to SSE.…”
Section: Discussionmentioning
confidence: 99%